Answer:
m = 6
Step-by-step explanation:
6m + 10 = 46
6m = 46 - 10
6m = 36
m = 36 : 6
m = 6
x = 1
x = 2
x = 5
x = 6
Answer: x = 6
Step-by-step explanation:
Let's solve your equation step-by-step.
81x=27x+2
Solve Exponent.
81x=27x+2
log(81x)=log(27x+2)(Take log of both sides)
x*(log(81))=(x+2)*(log(27))
x=(
log(27)
log(81)
)*(x+2)
x=0.75*(x+2)
x=0.75x+1.5(Simplify both sides of the equation)
x−0.75x=0.75x+1.5−0.75x(Subtract 0.75x from both sides)
0.25x=1.5
0.25x
0.25
=
1.5
0.25
(Divide both sides by 0.25)
x=6